Revitalization of Sharia Securities-Based Crowdfunding: A Regulatory Review and Its Impact on Halal MSME Development - Noor, Afif; Arifin, Moh.; Reza Fachruddin, Mohammad (Journal of Law, Politic and Humanities, 2024)
Sharia Securities-Based Crowdfunding (Sharia SBC) has significant potential in supporting the development of halal MSMEs in Indonesia. Halal MSMEs often face limited access to conventional financing The presence of Sharia SBC, based on information technology, can serve as an alternative source of funding in accordance with Sharia principles for halal MSMEs. This study aims to examine the regulations governing Sharia SBC and its impact on the development of halal MSMEs. The research method used is a qualitative approach with descriptive analysis. Data is collected from secondary sources such as literature studies, and analysis of regulatory documents. The results indicate that mature and comprehensive regulations are crucial to support the success of Sharia SBC. Existing regulations, such as the Financial Services Authority Regulation Number 57 of 2020 amended by OJK Regulation No. 16/POJK.04/2021 of 2021 provide a basic framework for the operation of Sharia SBCs. However, challenges persist, including the lack of Sharia financial literacy among MSMEs and investors, as well as the need to enhance technological infrastructure and accessibility of the SBC platform. Properly regulated, Sharia SBCs can enhance halal MSMEs' access to capital, thereby boosting their business growth and sustainability. Optimizing regulations and improving education and infrastructure are essential to maximizing the potential of Sharia SBC in supporting the development of halal MSMEs in Indonesia.